Development of Web E-Scaffolding Based on Scientific Explanation as Teaching Materials for Primary School Pre-service Teachers - Rizki Amelia (UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractScience learning does not only involve facts and concepts but also ways of thinking, explaining scientifically, and doing a practicum. Unfortunately, existing e-learning and/or social media have not been able to facilitate the implementation of online practicums. Therefore, an e-scaffolding website based on scientific explanations is needed as teaching media and materials since learning is mostly conducted online during the Covid-19 pandemic. This study aims to describe the development process and the validity and legibility of the e-scaffolding website to develop scientific explanations for elementary school pre-service teachers. The development of this e-scaffolding website refers to the development model developed by Lee and Owens (2004). The instrument of this study was a questionnaire using a Likert scale. There are 3 kinds of questionnaires used, including the material validation questionnaire by the expert validator, the media validation questionnaire by the expert validator, and the student readability test questionnaire. The results showed that the average product validation results on the website aspect were 84% and, on the e-scaffolding aspect was 86.67%. While the results of the product readability test were 82.29%. This means that the development of the e-scaffolding website based on scientific explanations is very valid and very feasible to use in developing the scientific explanation abilities of elementary school pre-service teachersKeywords: website e-scaffolding, scientific explanation, teaching materials.Â AbstrakDalam pembelajaran sains tidak hanya melibatkan fakta dan konsep, tetapi juga cara berpikir dan menjelaskan secara ilmiah. Selain itu, dalam pembelajaran sains juga membutuhkan praktikum. Sayangnya, e-learning atau media sosial yang ada belum dapat memfasilitasi pelaksanaan praktikum online. Oleh karena itu, dibutuhkan website e-scaffolding berbasis penjelasan ilmiah sebagai media dan bahan ajar di masa pandemi Covid-19. Penelitian ini bertujuan untuk mendeskripsikan proses pengembangan dan kevalidan serta keterbacaan website e-scaffolding untuk mengembangkan scientific explanation calon guru sekolah dasar. Pengembangan website e-scaffolding ini mengacu pada model pengembangan yang dikembangkan oleh Lee & Owens. Instrumen pengumpulan data berupa angket dengan menggunakan skala likert. Angket yang digunakan ada 3 macam, yaitu angket validasi materi oleh validator, angket validasi media oleh validator, dan angket uji keterbacaan siswa. Hasil penelitian menunjukkan bahwa rata-rata hasil validasi produk pada aspek website sebesar 84% dan pada aspek e-scaffolding sebesar 86,67%. Sedangkan hasil uji keterbacaan produk sebesar 82,29%. Hal ini berarti bahwa pengembangan website e-scaffolding berbasis penjelasan ilmiah sangat valid dan sangat layak digunakan dalam mengembangkan kemampuan penjelasan ilmiah calon guru sekolah dasar.Kata kunci: website e-scaffolding, penjelasan ilmiah, bahan ajar.